Penetration and Development of Meloidogyne javanica on Four Pistachio Rootstocks and Their Defense Responses - Shekari Mahoonaki Fatemeh; Mahdikhani Moghadam Esmat; Zakiaghl Mohammad; Pedram Majid (Journal of Nematology, 2023)
Pistachio yield is annually reduced due to root-knot nematode infections. In order to evaluate its resistance to Meloidogyne javanica, three domestic pistachio rootstocks, namely, Badami, Ghazvini and Sarakhs, and a wild pistachio, Baneh (Pistacia atlantica subsp. mutica), were selected. Their response to the nematode infection was evaluated based on different plant and nematode indexes, 120 days post-inoculation (dpi). The penetration and development rate of nematode in roots of these four pistachio rootstocks were evaluated at different time points by acid fuchsin staining. Based on the measured indexes, Badami, Ghazvini, Sarakhs, and Baneh rootstocks ranked as susceptible, moderately resistant, moderately resistant, and resistant, respectively. The penetration rate of second-stage nematode juveniles (J2) into four rootstocks was discussed. The first “midstage” or swollen juveniles appeared at 4 dpi but to a lesser extent in Ghazvini, Sarakhs, and Baneh cultivars. The first females were seen in Badami at 21 dpi, in Ghazvini and Sarakhs at 35 dpi, and in Baneh at 45 dpi. Three types of defense responses were distinguished and characterized in the examined pistachio rootstocks: (i) a hypersensitive response (HR)-like reaction in the cortex in Ghazvini, Sarakhs, and Baneh root tips at 4 dpi and 6 dpi; (ii) an HR response, degrading J2 which induce giant cells in the vascular cylinder of all rootstocks, at 6 dpi and 10 dpi; and (iii) an HR response, degrading females and giant cells in the vascular cylinder of all rootstocks at 15 dpi onward. These observations open new fields of study in breeding programs of this crop.